Universidade Técnica (UNITEC): instituição educacional de seleção, orientação e formação profissional - Santos, Thales Lobato dos (1980)
The aim of, the present work has double sense, at first, to suggest a kind of university directed more to the professional pra~ tce, selecting, orienting and educating the student through a Psicology Aplicated accompaniment, as well as to contribute with the middle and high leveI students, through a vew of the performance of the tea ching ruled by other universities of some countries in the world. The number of publications about universities 1S enough, especially in Brazil that put the men who study this in its form or functioning techniques. scanty subject There are meny works about the subject, but most them are restricted only to the inside acteves publications of the universities, most on the administrative and direction sense as well as statis tical divulgations of the number of the graduating students. without to mention however the fluxgrafc of its psycho-pedagogical structure. The work is rigorously well-based in the researches, observations and conclusions that como from many years of experien~e 1n teaching, not only in the middle leveI teaching area, including the 1n dustrial area, as in the high leveI teaching. This work has at first a conC1se view of the university e volution, completed by a detailed explanation of the teaching in many universities of the other contries, including their prerequisites. Another fundamental approaching is also done in the un1- versity relationship sense with the middle leveI professional technical teaching, approaching parallelly the importance of the work-market and the technological research. The aspects of the formation of the teachers and of the ' modernization and specialization for the third age related to their professional experience are approached. Finally is presented a new Kind of university we believe to be of high importance for the country, for the range of teaching areas that will be reached, conducting the students from the nursery school to the third age, with a trustful technical selection, a authe~ tic professional orientation and according with their dowries, as well as a realistic formation related to the science, the letters and the arts for each student. A comparison of the teaching in the technical university' proposed with the teaching followed by the other universities of the world, it facilitates a clearer vien for the work can't be considered as an arbitrary or 'utopian' summary which can deform the complex teaching reality, that exists until today.